The Development of Social Worker’s Professional Competence for Work with Youth Exposed to the Risk of Social Exclusion - Švalbe, Valentina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
To analyze contemporary leading socio-economic changes. The dynamic transition to a knowledge society, the growth of quality, quantity and volume of knowledge, technological, global scale (globalization) of political and social processes, as well as demographic changes are new challenges which require a new approach that involves all educational stages during the whole human life. The development of social worker's professional competence for work with young people exposed to the risk of social exclusion must be perceived multilaterally in contemporary Europe. They must be viewed in relation to the cultural diversity of people's economic and social rights, human rights, equality and gender equality of rights. The development of social worker's professional competence for work with young people exposed to the risk of exclusion does not mean only teaching, but it also includes life-long learning, mobility, integration, continuing education and other areas. The improvement of social worker's professional competence for work with young people exposed to the risk of exclusion is observed in adult activities related to professional activities. Analyzing the concept of competence, it is important to emphasize the idea of competence as the basis of an independent thinking and acting.